2015
DOI: 10.1093/nar/gkv1500
|View full text |Cite
|
Sign up to set email alerts
|

A genome landscape of SRSF3-regulated splicing events and gene expression in human osteosarcoma U2OS cells

Abstract: Alternative RNA splicing is an essential process to yield proteomic diversity in eukaryotic cells, and aberrant splicing is often associated with numerous human diseases and cancers. We recently described serine/arginine-rich splicing factor 3 (SRSF3 or SRp20) being a proto-oncogene. However, the SRSF3-regulated splicing events responsible for its oncogenic activities remain largely unknown. By global profiling of the SRSF3-regulated splicing events in human osteosarcoma U2OS cells, we found that SRSF3 regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 110 publications
10
113
1
Order By: Relevance
“…We searched the targets of SRSF3 in our previous splice array data (NCBI GEO accession no. GSE22149), in which osteosarcoma U2OS cells were treated with anti-SRSF3 or non-specific (NS) siRNA26. In the present study, we found that the expression level of hnRNP L decreased upon SRSF3 knockdown in U2OS cells (fold change: −1.98, p = 0.00516).…”
Section: Resultssupporting
confidence: 50%
“…We searched the targets of SRSF3 in our previous splice array data (NCBI GEO accession no. GSE22149), in which osteosarcoma U2OS cells were treated with anti-SRSF3 or non-specific (NS) siRNA26. In the present study, we found that the expression level of hnRNP L decreased upon SRSF3 knockdown in U2OS cells (fold change: −1.98, p = 0.00516).…”
Section: Resultssupporting
confidence: 50%
“…In addition to its regulation of viral gene expression, SRSF3 has been characterized as an oncogenic factor (66)(67)(68), and it effects global change of the gene expression of hundreds of mammalian genes to maintain cell homeostasis (34,39,(69)(70)(71). Upregulation and functional association with various types of cancer have been reported for SRSF3 (66)(67)(68)72) and hnRNP A1 (73-76), which we have identified here as two crucial trans-acting factors for alternative splicing of HPV18 pre-mRNAs.…”
Section: Discussionmentioning
confidence: 64%
“…To understand how the ESE functions in the promotion of RNA splicing, we analyzed the ESE sequence by searching for potential binding sites of trans-acting splicing factors that might regulate ESE function (11,34,(42)(43)(44)(45). As a result, we discovered that the identified ESE contains two putative SRSF3-binding motifs-SRSF3a, from nt 3522 to 3527, and SRSF3b, from nt 3539 to 3544 -and one putative SRSF1-binding A U1 binding motif of 11 nt (gray boxes) was attached to the 3= ends of pre-mRNAs 2, 4, 6, and 8 to enhance in vitro splicing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 20 potential osteosarcoma-associated proteins were selected to further validate the proteomic results. Among the 20 proteins, HUWE1, PCNA, GSN, ANXA1, AKAP12, and IDH2 have major roles in osteosarcoma tumorigenesis121314151617. MTHFD1, TSTA3, PGK1, HSPB1, MPST, HADHA, MCM5, CSE1L, LMNA, and MACF1 have been reported to be involved in tumorigenesis but not in osteosarcoma18192021222324252627.…”
Section: Resultsmentioning
confidence: 99%